2016
DOI: 10.3389/fmicb.2016.01003
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccin Induces M1 Polarization of Macrophages via Interaction with TLR4

Abstract: The fungal human pathogen Paracoccidioides brasiliensis contains paracoccin (PCN), a multi-domain protein that has lectin and N-acetyl-glucosaminidase activities, which account for its effects on the growth and morphogenesis of the fungus and on the activation of host macrophages through its interaction with TLR N-glycans. With the purpose of detailing the knowledge on the effects of PCN on macrophages, we used recombinant PCN expressed in Pichia pastoris (p-rPCN) to stimulate isolated murine peritoneal macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
2
26
0
3
Order By: Relevance
“…* p < 0.1. (B) Western blot analysis of a recombinant PCN protein, expressed in Pichia pastoris [48] and the PCN content in the supernatant of yeast cells that were co-cultured or not with THP-1 macrophages. Reactions were developed by IgY anti-PCN conjugated to HRPO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…* p < 0.1. (B) Western blot analysis of a recombinant PCN protein, expressed in Pichia pastoris [48] and the PCN content in the supernatant of yeast cells that were co-cultured or not with THP-1 macrophages. Reactions were developed by IgY anti-PCN conjugated to HRPO.…”
Section: Resultsmentioning
confidence: 99%
“…The response is triggered by the PCN lectin domain interaction with N-glycans of TLR2 and TLR4 [45, 47]. Both receptors are expressed on the surface of macrophages, which undergo M1 polarization followed by high production of pro-inflammatory mediators, such as the Th1 polarizing cytokine IL-12 [48]. We demonstrated that the developed Th1 immune response accounts for the host resistance to the P. brasiliensis infection conferred by the PCN administration [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the original use of lectins in vaccination protocols has been expanded to other applications. Hence, besides its use as therapeutic agents in infectious and parasitic diseases, lectins have been applied as new potential antineoplastic agents targeting apoptosis, autophagy, and anti-angiogenesis in preclinical or clinical trials for cancer therapeutics, and in neurodegenerative disorders, as well (Alegre-Maller et al, 2014; Bogoeva et al, 2014; Aminou et al, 2016; Barbosa-Lorenzi et al, 2016; Dar et al, 2016; Freitas et al, 2016; Ricci-Azevedo et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados contribuíram importantemente para elucidar os possíveis mecanismos responsáveis pelo efeito imunomodulador da PCN. A alta produção de IL-12 pelos macrófagos M1 e a decorrente diferenciação de células Th1, produtoras de IFNɣ, são responsáveis pela geração de resposta protetora contra P. brasiliensis, quando PCN é administrada na forma profilática ou terapêutica (Freitas, Oliveira et al 2016).…”
Section: Paracoccina De P Brasiliensis: Uma Quitinase Com Domínio Deunclassified
“…Estudos subsequentes utilizaram uma forma recombinante, denominada p-rPCN, que induziu macrófagos peritoneais murinos a produzirem mediadores pró-inflamatórios (IL-12p40, TNF-α, IL-6 e NO) e assumirem um perfil M1 de polarização. Tais efeitos de p-rPCN foram mediados por ligação da lectina a N-glicanos ligados ao exodomínio do receptor TLR-4, mas não de TLR2 (publicação inserida no capítulo I) (Freitas, Oliveira et al 2016). Além disso, p-rPCN induziu neutrófilos humanos a formarem NETs e liberarem IL-8 (publicação inserida no capítulo II) (Ricci-Azevedo, Goncales et al 2017).…”
Section: Considerações Finaisunclassified